HDL and glucose metabolism: current evidence and therapeutic potential - Siebel, Andrew L.; Heywood, Sarah Elizabeth; Kingwell, Bronwyn A. (Frontiers in Pharmacology, 2015)
High-density lipoprotein (HDL) and its principal apolipoprotein A-I (ApoA-I) have now been convincingly shown to influence glucose metabolism through multiple mechanisms. The key clinically relevant observations are that both acute HDL elevation via short-term reconstituted HDL (rHDL) infusion and chronically raising HDL via a cholesteryl ester transfer protein (CETP) inhibitor reduce blood glucose in individuals with type 2 diabetes mellitus (T2DM). HDL may mediate effects on glucose metabolism through actions in multiple organs (e.g. pancreas, skeletal muscle, heart, adipose, liver, brain) by three distinct mechanisms: i) Insulin secretion from pancreatic beta cells ii) Insulin-independent glucose uptake iii) Insulin sensitivity The molecular mechanisms appear to involve both direct HDL signaling actions as well as effects secondary to lipid removal from cells. The implications of glucoregulatory mechanisms linked to HDL extend from glycemic control to potential anti-ischemic actions via increased tissue glucose uptake and utilization. Such effects not only have implications for the prevention and management of diabetes, but also for ischemic vascular diseases including angina pectoris, intermittent claudication, cerebral ischemia and even some forms of dementia. This review will discuss the growing evidence for a role of HDL in glucose metabolism and outline related potential for HDL therapies.